Barriers for application of nursing research results among professional nurses in Songklanagarind Hospital - W Sangmanee (Journal of Health Science and Medical Research (JHSMR), 2006)
This survey research aimed to 1) describe the barriers for application of nursing research results among professional nurses, 2) compare perceived barriers for application of nursing research results between nurses who were and were not in an administrative position and 3) compare perceived barriers to the application of nursing research results among groups of nurses differing in terms of years of working, unit of working, experience in attending research training, conducting research and utilization of research results. The sample consisted of 221 registered nurses working in Songklanagarind Hospital. All nurses who had administrative position were included in the study. Stratified random sampling was employed to obtain nurses who were not in an administrative position. The research instrument consisted of two sections: Demographic data sheet and a modified form of the BARRIERS Scale, developed by Funk et al., scored from 1-4. Experts validated the content of the questionnaire. Cronbach's alpha coefficients for internal consistency of the total barrier scale was 0.95. Data were analyzed using percentage, mean, standard deviation and t-test. The findings revealed that the overall mean score of perceived barriers to the application of nursing research results among professional nurses was at a moderate level  ( X = 79.38, S.D. = 15.34). When taking four domains of barrier in application of research results into the consideration, it was found that mean score of all domains, namely barriers related to characteristics of research communication ( X = 21.38, S.D. = 4.67), barriers related to characteristics of research ( X = 20.15, S.D. = 4.84). barriers related to characteristics of organization ( X = 19.95, S.D. = 4.80), barrier related to characteristics of nurses ( X = 17.89, S.D. = 4.57) were also at moderate levels. There were significant differences in perceived barriers to the application of nursing research results between nurses who were in an administrative position and those who were not ( p < .05). Nurses who did not hold any administrative position were more likely to have a perceived higher barrier score than those who held administrative position. Moreover, there were significant differences in perceived barriers to the application of nursing research results between nurses who had experience in attending research training, conducting research, and utilizing research ( p < .05). Those who had no experience were more likely to have higher perceived barrier scores. There were no significant differences in perceived barriers to the application of nursing research results between nurses who differed in years of working or unit of working.